Health, mental health, music and music therapy in a Colombian indigenous community from Cota, 2012-2014 (2017)
Introduction: The intercultural approach to indigenous peoples in the American continent requires knowledge of the concepts and cultural practices that favor or impair health, considering their own perspective.Objective: To understand the meaning of health and mental health in the context of a Muisca community from Cota, Colombia, as well as the potential of music therapy to promote health.Materials and methods: Case study with a qualitative approach —social research of second order. Data collection included social cartography, in-depth interviews, focus groups, participant observation, and music therapy sessions.Results: This community has a different conception of health in relation to the beliefs of the dominant society, since health and mental health are not separate ideas. Music is integrated to community activities and health practice.Conclusions: The re-indigenization process is a political decision with cultural, health and organizational consequences. This type of communities cannot be equated with the dominant society or other indigenous groups in terms of health decisions. Public health requires an intercultural dialogue to work adequately with these communities.